Theoretical and experimental substantiation of a fungal therapeutic drug with immunomodulating and antitumor action according to the authors’ prescription - V. A. Кuchmistov; N. O. Коziko; O. F. Кuchmistova; O. P. Shmatenko; V. O. Таrasenko; A. O. Drozdova (Regulatory Mechanisms in Biosystems, 2018)
The article is devoted to a promising direction in pharmacological mycology and biotechnology, namely the use of Basidiomycetes as a biologically active substance for preparation of pharmaceuticals. The anticancer and immunostimulating properties of Basidiomycetes result from the structural characteristics of the polysaccharides: the presence of β-(1 → 3) connections in the main chain and an additional β-(1 → 6) branched part of glucans. Attention is focused on Shiitake mushrooms (Lentinula edodes) as a unique biosystem with a strong ability to be involved in the regulatory mechanism of human immunomodulation. The purpose of the theoretical and experimental study is development of a pharmaceutical preparation from Shiitake biomass (including its immune cells), the effectiveness of which is considered from the standpoint of the chemistry of natural compounds. Having a 3000-year history of cultivation and application, this mushroom is again of interest to scientists around the world because of investigation into its therapeutic and prophylactic potentials. For the first time, the biotechnological method of cultivating L. edodes biomass was developed with the use of deep cultivation, adapted to the plant raw material base of Ukraine. Malt wort was used as a nutrient medium without processing Humulus lupulus. The analysis of research and preclinical studies of specific activity of the designated biosystem showed a steady increase in human immune status, particularly the antitumor status. This gives special relevance to the evaluation of the properties of the designated biosystem in order to further develop the corresponding fungo-therapeutic immunomodulatory and antitumor drug. According to the results of technological research: physico-chemical characteristics of Shiitake biomass dry powder (including crystallographic) were studied; the possibility of its tableting using only antifriction auxiliaries was substantiated; the optimum technology of tablet manufacturing with an operating name "Shitavit" was presented, an integrated approach to its creation was presented, the qualitative and quantitative composition of the drug was experimentally developed. The direct compression method was rejected due to unsatisfactory performance of all samples of tablets. The chosen technology of using preliminary granulation and the possibility of short-term contact of the L. edodes dry powder with a granulation liquid and an adjustable temperature regime allows all the properties of the biologically active substances of the designated raw material to be preserved. The research results for all series of the designated object showed relative stability of parameters for all indicators in laboratory samples. The information presented in this article is a guide to further research, necessary for a better understanding of the healing properties of fungal polysaccharides, increasing the use of broad-spectrum fungi-based preparations,leading to improvement of the quality of human life.